Spanish in the colonial Andes: texts, authors and discourses - Huamanchumo de la Cuba, Ofelia (2012)
When more than 500 years ago the Spanish language spread to its colonies in America, a shortcut to a fascinating detour suddenly opened up along the path that its history seemed to travel. In this new stretch taken towards the Indies, the language of the Catholic kings would run into the most diverse cultures and their languages, several of which developed in the imposing geography of the South American Andes. This truth aroused from its birth the practical interest of the evangelizers, coming from a humanistic Europe that had already begun the production of grammars of the Romance languages ​​and other exotic languages. For the rest, the Amerindian languages ​​continued to sharpen the sharpness in the gaze of scholars of later times. Leading linguists, philologists and historians of language and literature from different universities around the world have also taken a look at this part of the history of Spanish. They have also been joined by specialists from other disciplines, Americanists and Peruvianists, who with their research have been demonstrating the relevance of interdisciplinary work.